1998
DOI: 10.1007/s003830050235
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus conventional appendectomy in children

Abstract: Over a period of 6 months, 48 children who underwent conventional appendectomy (CA) were compared to 34 children who had laparoscopic appendectomy (LA) for acute and recurrent subacute appendicitis. Their ages ranged from 4 to 12 years (mean 8). LA took significantly longer, 76 min, versus 50 min for CA. Less than 2 days' hospitalization was required in 95% of LA cases and 45% of CA cases. Time to return to normal activity averaged 7 days for LA and 12 days for CA (P < 0.001). Wound complications were fewer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
2
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 10 publications
1
32
2
3
Order By: Relevance
“…The abscess rate was slightly higher in the laparoscopic group, but the difference was not statistically significant. Some studies included in metaanalysis showed less need for postoperative analgesia [11,13,14] and better cosmetic effect [10] as additional advantages of laparoscopy, so the main negative feature of laparoscopic appendectomy remains the higher cost [18]. For that reason, an idea to apply principles and strategies of both procedures and thus compile advantages, resulted in development of laparoscopically assisted techniques.…”
Section: Discussionmentioning
confidence: 97%
“…The abscess rate was slightly higher in the laparoscopic group, but the difference was not statistically significant. Some studies included in metaanalysis showed less need for postoperative analgesia [11,13,14] and better cosmetic effect [10] as additional advantages of laparoscopy, so the main negative feature of laparoscopic appendectomy remains the higher cost [18]. For that reason, an idea to apply principles and strategies of both procedures and thus compile advantages, resulted in development of laparoscopically assisted techniques.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the purported reduction in postoperative pain after laparoscopy has not been confirmed in randomized studies [11]. Laparoscopic appendectomy (LA) does provide the opportunity to evaluate and visualize the entire abdominal cavity in cases of diagnostic dilemmas [7], and with cost-conscious use of reusable instruments, the procedure is no more expensive than its open counterpart [15].…”
mentioning
confidence: 99%
“…Appendectomy is one of the most common intraabdominal surgical procedures in children [7]. Laparoscopic appendectomy (LA), first performed by Semm in 1983 [21], has gained popularity among adult and pediatric surgeons but is still subject to controversy.…”
mentioning
confidence: 99%